2009
DOI: 10.1186/1471-2229-9-45
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle penetration and transport in living pumpkin plants: in situsubcellular identification

Abstract: Background: In recent years, the application of nanotechnology in several fields of bioscience and biomedicine has been studied. The use of nanoparticles for the targeted delivery of substances has been given special attention and is of particular interest in the treatment of plant diseases. In this work both the penetration and the movement of iron-carbon nanoparticles in plant cells have been analyzed in living plants of Cucurbita pepo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(189 citation statements)
references
References 27 publications
10
174
0
5
Order By: Relevance
“…The recorded increase in Chl a, Chl b and carotenoids was in harmony with that found by Tripathi et al (2015) in pea seedlings under Cr stress by silicon oxide nanoparticles. This enhancement may be due to that Zn plays an important role in chlorophyll synthesis (Corredor et al, 2009), chloroplast structure, photosynthetic electron transfer (Fathi et al, 2017). The recorded increase in total soluble carbohydrates and protein on priming with Nano ZnO was in accordance with the findings of Venkatachalam et al (2016) using Nano ZnO under Cd or Pb stress in Leucaena leucocephala seedlings and with those of Soliman et al (2015) using nano-iron and nano-zinc in salt stressed Moringa peregrina plants.…”
Section: Discussionsupporting
confidence: 80%
“…The recorded increase in Chl a, Chl b and carotenoids was in harmony with that found by Tripathi et al (2015) in pea seedlings under Cr stress by silicon oxide nanoparticles. This enhancement may be due to that Zn plays an important role in chlorophyll synthesis (Corredor et al, 2009), chloroplast structure, photosynthetic electron transfer (Fathi et al, 2017). The recorded increase in total soluble carbohydrates and protein on priming with Nano ZnO was in accordance with the findings of Venkatachalam et al (2016) using Nano ZnO under Cd or Pb stress in Leucaena leucocephala seedlings and with those of Soliman et al (2015) using nano-iron and nano-zinc in salt stressed Moringa peregrina plants.…”
Section: Discussionsupporting
confidence: 80%
“…Corredor et al found nanoparticle penetration into the first cell layer of pumpkin plants (20). In order to increase the understanding between the nanoparticles and the leaf surface, we incorporated maize leaves into a well characterized ceria suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleation mode particles exhibit high deposition velocities to forest canopies due to their high Brownian diffusion velocities, the large surface area of forests and enhancement of particle capture efficiencies due to leaf micro-texture . There is also evidence that nano-particles may penetrate leaves via the stomata (Burkhardt et al, 2012;Corredor et al, 2009). Actual deposition velocities (surface capture) to forests are complex functions of factors such as leaf orientation, and the key leaf characteristics (width, length and thickness) are variable by species.…”
Section: Introduction and Objectivesmentioning
confidence: 99%